Treatment of Acetabulum Fractures Through the Modified Stoppa Approach: Strategies and Outcomes - Isaacson, Mark J. (Springer US, 2014)
BACKGROUND: Since the original description by Letournel in 1961, the ilioinguinal approach has remained the predominant approach for anterior acetabular fixation. However, modifications of the original abdominal approach described by Stoppa have made another option available for reduction and fixation of pelvic and acetabular fractures. QUESTIONS/PURPOSES: We evaluated our results in patients with acetabulum fractures with the modified Stoppa approach in terms of (1) hip function as measured by the Merle d’Aubigne hip score; (2) complications; and (3) quality of fracture reduction and percentage of fractures that united. METHODS: Between September 2008 and August 2012, 289 patients with acetabular fractures were treated at our Level I trauma center. Twelve percent (36 of 289) of patients were treated operatively using the modified Stoppa approach. Ninety-seven percent (35 of 36) of our patients had fracture patterns involving displacement of the posterior column. Six (17%) were converted early to a total hip arthroplasty, and 14 (39%) were lost to final followup, leaving 22 of 36 for subjective clinical outcome analysis at a mean of 32 months (range, 9–59 months). Our general indications for this approach during the period in question were fractures of the anterior column and anterior wall, anterior column with posterior hemitransverse fractures, both column fractures, transverse fractures, and T-type fractures. Followup included regularly scheduled office visits with radiographs (AP pelvis, Judet views) that were graded by the treating surgeon and by the authors of this study (MJI, BCT) and patient outcome surveys. RESULTS: Merle d’Aubigne hip scores were very good in 55% (12 of 22), good in 9% (two of 22), medium in 18% (four of 22), fair in 5% (one of 22), and poor in 14% (three of 22), and 70% (23 of 33) of patients were able to ambulate without any assistive devices. Complications included one superficial infection and three deep infections, two patients with temporary lateral thigh numbness, no obturator nerve palsies, and one inguinal hernia. Three deaths in the cohort were seen in followup as a result of unrelated causes. Radiographic grading of fracture reductions after surgery revealed that 27 (75%) were anatomic, six (17%) were satisfactory, and three (8%) were unsatisfactory. A total of 94% of the fractures united. CONCLUSIONS: In agreement with prior published data, our results show good functional outcomes with minimal complications using the modified Stoppa approach for a variety of acetabular fractures. Our results highlight the difficulty but feasibility in treating posterior column displacement through an anterior approach. Consideration for dual approaches with posterior column involvement may be warranted to optimize fracture reduction and functional outcomes. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.